Christian Social Practice in a Context of HIV/AIDS-related Stigmatisation in Tanzania - Mligo, Elia Shabani (Diaconia, 2012)
Bible reading and compassionate practices play important roles in church related work for people living with HIV and AIDS in Africa. Those who are affected by this disease experience stigma and exclusion; so compassion is both relevant and important. But the Bible has to be read with the intention to reduce the power relation between the Bible reading experts and the non-experts. This is a challenge for the Ujamaa Centre in South Africa.
Paid
Keywords: AIDS (Disease); Africa – Health conditions; Bible – Study and teaching; Church work with the sick; Compassion – Religious aspects – Christianity; Contextual Bible study; HIV (Viruses); Peer reviewed; Sick – Religious life; Spiritual care (Medical care); Stigma (Social psychology); Tanzania – Health conditions; Theology; Contextual